Better us later than me now: Regulatee-size and time-inconsistency as determinants of demand for environmental policies - Marius Alt (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
To adequately design and implement effective environmental policies, it is paramount for policymakers to understand preferences for regulatory instruments as well as their individual level determinants. In this study, I experimentally investigate the demand for three environmental policies, comprising nudges, monetary incentives, and punishments. I elicit the demand for these interventions through decisions in a pro-environmental real effort task. The experiment introduces exogenous variation along two dimensions to analyze, whether interventions are (1) demanded as commitment devices to commit to future pro-environmental behavior, and (2) how demand changes when regulation affects not only the self but also others. The results show that a large fraction of individuals demands regulation, which is, however, heterogeneously distributed across participants, being dependent on individual characteristics. Moreover, particularly participants who are sophisticated about their time-inconsistent prosocial preferences demand interventions to commit to pro-environmental behavior. When the intervention is also imposed on other participants, this leads to an increase in the demand, driven by conditionally cooperative individuals who are not averse to constraining others' behavior. Finally, I provide evidence that the experimentally elicited demand for interventions can serve as a predictor of preferences for actual environmental policies.
Keywords: Q58; D04; C91; 330; Pro-environmental behavior; Nudges; Economic incentives; Real effort